The wild one - Farley, Terri (Farley, Terri. Phantom stallion, 2023)
The beloved first book in the middle grade Phantom Stallion series about a girl, her horse, and the beauty of the American West returns with a brand-new, stunning cover and bonus material! Perfect for fans of Canterwood Crest and classic horse stories like Black Beauty and My Friend Flicka. When thirteen-year-old Samantha returns home to her family’s cattle ranch in Nevada, she’s nervous. She moved away two years ago to recover from a bad fall off her beloved mustang, Blackie, and she’s still not sure she can get back in the saddle. She’s having trouble bonding with her new horse, Ace, the other ranchers treat her like the boss’s spoiled daughter, and Blackie has been missing since the day of Sam’s fateful accident. But that’s just the beginning. On a moonlit night, a mustang comes to Sam. Is it Blackie grown up and gone wild—or the legendary phantom stallion? When Sam suddenly finds the fate of the horse resting in her hands, she has to be a real cowgirl, ready or not.